2009
DOI: 10.1159/000229776
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Parkinsonism in an Amish Community

Abstract: Background: Parkinson’s disease (PD) is a neurodegenerative disorder with unknown cause. Genetic mutations account for a minority of cases but the role of environmental factors is unclear. Methods: We performed a population-based screening for PD in subjects in an Amish community over age 60. PD was diagnosed using standard clinical criteria and the Unified Parkinson Disease Rating Scale motor subsection 3 (UPDRS3). Community prevalence was calculated. We constructed a community pedigree and calculated kinship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
1
12
2
Order By: Relevance
“…Contrary to our initial hypothesis based on results from other Amish communities [4,5], we found that the prevalence of clinical PD diagnoses (1.2%) to be similar to that reported in the general U.S. older adult populations [6]. For those without a PD diagnoses, the prevalence of motor symptoms defined as positive for at least one nine-item motor questionnaire to screen for PD (10.5%) is not higher than the general population based on based on face-face exam in older populations (16%-48%) [15,16] farming, manual labor) that may decrease constipation [10].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our initial hypothesis based on results from other Amish communities [4,5], we found that the prevalence of clinical PD diagnoses (1.2%) to be similar to that reported in the general U.S. older adult populations [6]. For those without a PD diagnoses, the prevalence of motor symptoms defined as positive for at least one nine-item motor questionnaire to screen for PD (10.5%) is not higher than the general population based on based on face-face exam in older populations (16%-48%) [15,16] farming, manual labor) that may decrease constipation [10].…”
Section: Discussioncontrasting
confidence: 99%
“…In a community-based survey of 4,369 Amish in Missouri, Racette et al [4] reported that 7% of 213 participants older than 60 years met the criteria of clinical diagnosis of PD and 35% had subclinical parkinsonian signs based on Unified PD Rating Scale-Part III motor (UPDRS) exams. Similarly, Cummings et al [5] reported a prevalence of ~5% (33/647) for clinical PD in Amish subjects ≥60 years old from Indiana and Ohio.…”
Section: Introductionmentioning
confidence: 99%
“…GM volume has also been associated with more severe measures of motor dysfunction (bradykinesia and gait disturbance), which is prevalent even among older adults without neurological conditions [42,51,52]. Among 307 community-dwelling older adults (mean age=83) without PD, smaller GM sensorimotor cortical and posterior parietal lobe volumes were associated with bradykinesia and gait disturbance.…”
Section: Grey Matter (Gm)mentioning
confidence: 99%
“…Because the method of ascertainment of cases was different in these studies, the obtained prevalence ratio (10.19) reported in this study is unlikely to be valid. A more recent study by the same investigators 56 showed that utilization of a similar method to that used to assess parkinsonism in Alabama welders generated a very high rate in the general population as well, bringing into question the conclusion from the Alabama welding study that welders have higher risk of PD.…”
Section: Association Between Exposure To Manganese and Pdmentioning
confidence: 99%